Academic intelligence, emotional intelligence and creative capacities in students with different level of school achievements - Karwowski, Maciej (Studia Psychologica: Theoria et praxis, 2004)
The attempt has been undertaken to verify some hypotheses on links between four variables: „academic” intelligence, emotional intelligence, creative attitude and school achievements. The group of 561 students from Warsaw high schools has been tested. The experiment has been done with the use of INTE Questionnaire, Ravens Progressive Matrix and Test of Creative Thinking – Drawing Production. Results suggest that the factor with the strongest influence on school achievement is participants’ gender. Binary logistic regression also showed that only “academic” intelligence has important influence on school grades – weak, but significant from the point of view of statistics.